Odpowiedź :
Odpowiedź:
a) xs = [tex]\frac{-5 + 3}{2}[/tex] = - 1 ys = [tex]\frac{-2 + 8}{2}[/tex] = 3
S = ( -1, 3) B = (3, 8)
r² = I SB I² = ( 3 + 1)² + ( 8 - 3)² = 4² + 5² = 16 + 25 = 41
( x - xs)² + ( y - ys)² = r²
więc
Odp. ( x + 1)² + ( y - 3)² = 41
=============================
b) ( x + 3)² + ( y - 1)² = 100
r = 10
A =( 5, 7)
y = a x + b A = ( 5, 7)
więc
7 = 5 a + b ⇒ b = 7 - 5 a
y = a x + 7 - 5 a - ta prosta ma być styczna w A =( 5, 7), więc
jej odległość od S = ( -3, 1) musi być równa r = 10
a x - y + 7 - 5 a = 0
[tex]\frac{ I -3 a - 1 + 7 - 5 a I}{\sqrt{a^1 + 1} } = 10[/tex]
I - 8a + 6 I = 10 ( [tex]\sqrt{a^2 + 1}[/tex] )
(- 8 a + 6)² = 100 a² + 100
64 a² - 96 a + 36 = 100 a² + 100
36 a² + 96 a + 64 = 0 / : 4
9 a² + 24 a + 16 = 0
Δ = 576 - 4*9*16 = 576 - 576 = 0
a = [tex]\frac{- 24}{18}[/tex] = - [tex]\frac{4}{3}[/tex]
y = - [tex]\frac{4}{3}[/tex] x + 7 - 5*( - [tex]\frac{4}{3}[/tex] )
y = - [tex]\frac{4}{3}[/tex] x + 13 [tex]\frac{2}{3}[/tex]
=================
Szczegółowe wyjaśnienie: